The Impact of Electronic Educational Broadcasting on the Development of English Listening Skills for Primary Students Sixth Grade - Al-Sahali, Seetah Mohammed Abdullah; Al-Shehri, Ajlan Mohammed (Journal of Curriculum and Teaching Methodology, 2023)
The aim of current study is to identify the impact of electronic educational Broadcasting of English Listening Skills for Primary Students Sixth Grade. The study used the quasi- experimental approach. The study sample consisted of (30) students from the sixth grade of primary school, in 314 primary school in the east of Riyadh city, and the sample was divided into two groups: an experimental group, numbering (15) students, and a control group, numbering (15) students, and the study used the achievement test as a tool for the study. The degrees of the experimental group and the control group in the post- application of the achievement test in favor of the experimental group, which indicates the existence of a significant effect of electronic educational broadcasting on developing listening skills in the English language course for sixth grade students. The study recommended many recommendations, the most important of which are: The use of electronic educational broadcasting in education because of its feasibility in developing the listening skills of the English language course among students of the sixth grade of primary school and encouraging the students towards the use of technology. Modern intention in education, and the development of their self- learning by using technology, and not being satisfied with classroom lessons, Urging English language teachers to pay attention to the listening skills of the English language course through educational audio clips, because these skills have an essential role in the learning process, work to reduce the obstacles that teachers face in using modern technology and facilitate access to them, the need to pay attention to the development of listening skills for the English language course among various educational stages, especially the primary stage.